ODIN: Clustering Analysis of 14,000 Lyα-emitting Galaxies at z = 2.4, 3.1, and 4.5 - Danisbel Herrera; Eric Gawiser; Barbara Benda; Nicole M. Firestone; Vandana Ramakrishnan; Byeongha Moon; Kyoung-Soo Lee; Changbom Park; Francisco Valdes; Yujin Yang; María Celeste Artale; Robin Ciardullo; et al. (The Astrophysical Journal Letters)
Ly α emitters (LAEs) are star-forming galaxies that efficiently probe the spatial distribution of galaxies in the high-redshift Universe. The spatial clustering of LAEs reflects the properties of their individual host dark matter halos, allowing us to study the evolution of the galaxy–halo connection. We analyze the clustering of 5233, 5220, and 3706 LAEs at z = 2.4, 3.1, and 4.5, respectively, in the 9 deg ^2 COSMOS field from the One-hundred-deg ^2 DECam Imaging in Narrowbands survey. After correcting for redshift-space distortions, LAE contamination rates, and the integral constraint, the observed angular correlation functions imply linear galaxy bias factors of b = $1.7{2}_{-0.27}^{+0.26},2.0{1}_{-0.29}^{+0.26},$ and $2.9{5}_{-0.46}^{+0.40}$ for z = 2.4, 3.1, and 4.5, respectively. The median dark matter halo masses inferred from these measurements are ${log}(M_{h}/M_{\odot })$ = $11.4{4}_{-0.28}^{+0.30},\,11.1{3}_{-0.26}^{+0.26},\,and\,10.8{5}_{-0.24}^{+0.24}$ for the three samples, respectively. The analysis also reveals that LAEs occupy roughly 3%–7% of the halos whose clustering strength matches that of the LAEs.